Exploring of Insertion/deletion Polymorphism in the Vascular Endothelial Growth Factor Gene Associated with Type 2 Diabetic Patients in Al-Diwaniyah City - Mohanad Jawad Kadhim (Journal of Global Pharma Technology, 2018)
Disease conditions that are related to the effects of the vascular endothelial growth factor (VEGF) are common such as nephropathy and promoting of cancer growth and metastasis. The current study was launched to explore the presence of VEGF gene-based polymorphism of the insertion/deletion (I/D) in blood samples of 25 diabetic and 25 clinically healthy people in Al-Diwaniyah City, Iraq. Using polymerase chain reaction (PCR), the results have shown the presence of these genotypes in these samples with higher significant (p˂0.05) occurrence. The homozygous DD was significantly (p˂0.05) affected by the sex factor. This genotypic characteristic was shown significantly (p˂0.05) in females more than that in males. Moreover, this feature was significantly higher (p˂0.05) when compared to the other genotypes II and I/D for each of the females or males separately. For the DD genotype, ages between 40 to 49 years of old have shown significantly (p˂0.05) higher presence of this genotype than that in other ages. It has been also shown by these results that this genotype is present significantly (p˂0.05) higher than that in the other genotypes when compared together in each age category. These results suggest current relationship between the VEGF I/D polymorphism occurrence and diabetes with deeper correlation with sex and age factors.Keywords: VEGF I/D polymorphism, diabetes, sex, age.